PS 05-37 MALNUTRITION, RENAL DYSFUNCTION, AND LEFT VENTRICULAR HYPERTROPHY SYNERGISTICALLY INCREASE THE LONG-TERM INCIDENCE OF CARDIOVASCULAR EVENTS. (September 2016) - Maruyama, Keisuke; Nakagawa, Naoki; Saito, Erika; Matsuki, Motoki; Takehara, Naofumi; Akasaka, Kazumi; Sato, Nobuyuki; Hasebe, Naoyuki
Abstract : Objective: This study investigated the impact of malnutrition, low estimated glomerular filtration rate (eGFR) and left ventricular hypertrophy (LVH) on cardiovascular events in a long-term observational study. Design and Method: Among 338 patients aged 40–80 years who underwent echocardiographic evaluation between 2003 and 2005, 161 patients followed up for >7 years were recruited. Echocardiographic LVH was defined as left ventricular mass index (LVMI) ≥ 125 g/m 2 for men and ≥ 110 g/m 2 for women. The geriatric nutritional risk index (GNRI) was used to assess the nutritional status of the patients and was calculated using the following formula: GNRI = (14.89 × serum albumin) + [41.7 × (body weight / body weight at BMI of 22)]. Malnutrition was defined as GNRI ⩽ 96. Results: Mean age was 63.5 ± 9.2 years, mean eGFR: 72.9 ± 18.7 ml/min/1.73m 2, mean GNRI: 100.4 ± 6.0 and mean LVMI: 114 ± 33 g/m 2 . The number of patients with eGFR <60 ml/min/1.73m 2, GNRI ⩽ 96 and LVH was 40 (25%), 32 (20%) and 59 (37%), respectively. During the follow-up period (median: 95 months), cardiovascular events were recorded in 15 patients (9%), including 7 acute coronary syndromes, 4 heart failures, 2 strokes, 1 aortic dissection and 1 aortic rupture. Kaplan-Meier curves showed a significantly higher incidence in patients with eGFR < 60 mL/min/1.73m 2 (log rank P = 0.007), GNRI ⩽ 96 (P = 0.003), or LVH (P = 0.010) (Figure 1). In Cox proportional hazards analysis, Age, eGFR, LVH, and GNRI were sifnificantly associated with cardiovascular events after adjusting for gender, hemoglobin level, and the prevalence of hypertension and diabetes (Table 1). Conclusions: Malnutrition, low eGFR, and LVH were independent determinants of cardiovascular events; they synergistically increased rates of these events in the long term. It is important to evaluate and manage the progression of LVH and improve nutritional status even in non-dialysis patients.